Ropivacaine suppresses tumor biological characteristics of human hepatocellular carcinoma via inhibiting IGF-1R/PI3K/AKT/mTOR signaling axis. Issue 2 (20th December 2021) - Zhang, Runze; Lian, Yanhong; Xie, Kangjie; Cai, Yunfang; Pan, Yafei; Zhu, Yuntian
ABSTRACT: Ropivacaine, a common local anesthetic in the clinic, has anti-proliferative and pro-apoptotic effects in numerous cancers, however, the underlying regulatory mechanism of ropivacaine in hepatocellular carcinoma remains unclear. In the current study, human HepG2 cells were stimulated with different ropivacaine concentrations. Cell Counting Kit-8 assay, cell colony formation, and cell cycle were used to monitor cell viability. Cell apoptosis, migration, and invasion were determined by flow cytometry and transwell assays. Tumor xenograft experiments were performed to prove the anti-cancer effect of ropivacaine in vivo . A high dose of ropivacaine inhibited proliferation and promoted apoptosis of HepG2 cells in a dose-dependent manner. Ropivacaine challenge also arrested cells in the G2 phase, followed by a decline in the protein expression of cyclin D1 and cyclin-dependent kinase 2, and an increase in p27 levels in HepG2 cells. Additionally, different ropivacaine doses suppressed cell migration and invasion by upregulating E-cadherin expression and downregulating N-cadherin expression. Mechanically, ropivacaine challenge gradually restrained insulin-like growth factor-1 receptor (IGF-1 R) expression and the activities of phosphorylated-PI3K, AKT, and mTOR in HepG2 cells with increased ropivacaine doses. In the tumor xenograft experiment, ropivacaine was confirmed to inhibit tumor growth, accompanied by inhibition of the IGF-1 R/PI3K/AKT/mTOR signaling axis. In conclusion, ropivacaine suppressed tumor biological characteristics and promoted apoptosis, resulting in the suppression of hepatocellular carcinoma progression by targeting the IGF-1 R/PI3K/AKT/mTOR signaling pathway. It is possible that ropivacaine-mediated local anesthesia may be developed as a novel surgical adjuvant drug for treating hepatocellular carcinoma. Graphical Abstract: uf0001